(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
In the past few years, it has been observed that organization are dependent on on technology in the field of Human Resources(HR). Every vertical of HR is using technology for the sake of better time management, efficiency in working, for being productive, handling the compensation, evaluating the employees, hiring the candidate through the online means etc. All of this require technology and in this qualitative study the author has tried to gather the technologies used in all the verticals, and there impact on the HR functioning and how Human Resource Information System(HRIS) is being used in the organization, and its effect on the overall functioning of the HR department. Over the years HR has moved from the lower level of management, administrative and maintenance work to a core business and strategic level, this was only possible as the technology came into existence, data analytics took decision making to another level, and HRIS has modified HR administrative work and enhanced the business.